What Opportunities and Challenges Were Given for Digital Transformation In 2020? Reasoning the Digital Change Impacted By COVID-19 In Europe. - Kamila TRATKOWSKA; Grzegorz TRATKOWSKI (Communications of International Proceedings, 2021)
This paper studies the digital transformation in a business environment and education sector in the context of the COVID-19 pandemic. There is a vast range of practices and technologies used to cope with the pandemic. Organizations were forced to rethink their management systems and reengineer the processes. Even the businesses that had remained reluctant to introduce flexibility in operation and adopt new technologies before COVID-19, got a brief lesson of change and crisis management. People were made to convert daily routines, switch to the remote, and reorganize themselves in many spheres of life. To this end, analysis of the impact on worldwide, agile projects whose main aim is to mitigate the crisis because of the virus outbreak.
Keywords: Digital transformation; technology; new ways of working; education; pandemic; COVID-19